Strand-Specific Patterns of Codon Usage Bias Across Cressdnaviricota - Crespo-Bellido, Alvin; Duffy, Siobain (Frontiers in Virology, 2022)
The rapidly expanding phylum Cressdnaviricota contains circular, Rep-encoding single-stranded (CRESS) DNA viruses that are organized within seven established families, but many CRESS DNA virus sequences are not taxonomically defined. We hypothesized that genes in Cressdnaviricota ambisense genomes exhibit strand-specific signatures due to a cytosine to thymine transition bias that can help determine the orientation of the genome: which strand is packaged and is in the “virion sense”. To identify broad strand-specific patterns across genera, we performed compositional analyses of codon usage across the two major opposite sense open reading frames of 712 reference genomes. Additionally, we developed a statistical test to identify relative codon overrepresentation between ambisense sequence pairs for each classified virus exemplar and an additional 137 unclassified CRESS DNA virus genomes. Codons clustered by the identity of their third-position nucleotide, showing both strand- and genus-specific patterns across Cressdnaviricota. Roughly 70% of virion-sense sequences have a relative overrepresentation of thymine-ending codons while ~80% of anti-sense sequences display a relative overrepresentation of adenine-ending codons (corresponding to increased thymine in these genes as packaged). Thirteen of the 137 unclassified viruses show strong evidence of having the rarer circovirus-like genome orientation, and likely represent novel genera or families within Cressdnaviricota. Given the strong strand-specific patterns of relative codon overrepresentation, the results suggest that the relative codon overrepresentation test can serve as a tool to help corroborate the genome organization of unclassified CRESS DNA viruses.